Electrochemical Delamination of Ultralarge Few‐Layer Black Phosphorus with a Hydrogen‐Free Intercalation Mechanism. Issue 1 (27th November 2020) - Wang, Ning; Mao, Nannan; Wang, Zhien; Yang, Xue; Zhou, Xi; Liu, Haining; Qiao, Shanlin; Lei, Xingfeng; Wang, Junru; Xu, Hua; Ling, Xi; Zhang, Qiuyu; et al.
Abstract: Due to strong interlayer interaction and ease of oxidation issues of black phosphorus (BP), the domain size of artificial synthesized few‐layer black phosphorus (FL‐BP) crystals is often below 10 µm, which extremely limits its further applications in large‐area thin‐film devices and integrated circuits. Herein, a hydrogen‐free electrochemical delamination strategy through weak Lewis acid intercalation enabled exfoliation is developed to produce ultralarge FL‐BP single‐crystalline domains with high quality. The interaction between the weak Lewis acid tetra‐ n ‐butylammonium acetate (CH3 COOTBA) and P atoms promotes the average domain size of FL‐BP crystal up to 77.6 ± 15.0 µm and the largest domain size is found to be as large as 119 µm. The presence of H + and H2 O is found to sharply decrease the size of as‐exfoliated FL‐BP flakes. The electronic transport measurements show that the delaminated FL‐BP crystals exhibit a high hole mobility of 76 cm 2 V –1 s –1 and an on/off ratio of 10 3 at 298 K. A broadband photoresponse from 532 to 1850 nm with ultrahigh responsivity is achieved. This work provides a scalable, simple, and low‐cost approach for large‐area BP films that meet industrial requirements for nanodevices applications. Abstract : Ultralarge few‐layer black‐phosphorus single crystals are obtained with a hydrogen‐free electrochemical exfoliation mechanism using CH3 COOTBA intercalation. The largest size is up to 119 µm with an average around at 77.6 ± 15.0 µm. A high hole mobility of 76 cm 2 V –1 s –1, and a broadband photoresponse from 532 to 1850 nm with ultrahigh responsivity are achieved at 298 K.